Viscosity of Polycaprolactone Microplastic Dispersions and Nonlinear Kinetic Models of Plastic Fragmentation - Vincenzo Villani; Pier Luigi Gentili (Molecules)
Viscosimetric experiments and microscopy measurements on microdispersions of polycaprolactone (PCL) plastics showed an unexpected exponential decrease in viscosity over the first 3 months and a plateau for a further 4 months of observations. This behavior is due to the release of nanoplastics from semicrystalline particles that reduce the viscosity of the dispersion, and leave stable and fine crystalline microplastics ranging in size from 30 to 180 μm. The development of nonlinear kinetic models for the fragmentation process from macro- to meso-, micro-, and nanoplastics reveals complex behavior that we call a cracking–leaching mechanism. The autocatalytic mechanical cracking of macroplastics larger than 5 mm is followed by a logistic-type mechanical cracking of mesoplastics between 5 and 1 mm. Therefore, microplastics smaller than 1 mm experience the leaching diffusion modeled via nonlinear coupled kinetic differential equations: semicrystalline microplastics quickly release nanoplastics from the amorphous fraction, followed by fine and stable crystalline microplastics. This proposed mechanism explains the size distribution of floating plastic debris in the oceans, with an unexpected gap of microplastics. Considering the outcome, a general reflection is made on the critical issues that currently appear unsolvable regarding plastic pollution.